Venous Thrombosis Following the Use of Intermediate Purity FVIII Concentrate to Treat Patients with Von Willebrand’s Disease - Makris, M.; Colvin, B.; Gupta, V.; Shields, M. L.; Smith, M. P. (Thrombosis and Haemostasis, 2002)
We describe four patients with von Willebrand’s disease (VWD) who experienced venous thrombosis after treatment with an intermediate purity factor VIII (FVIII) concentrate (Haemate P®) was used to cover invasive or surgical procedures. Most patients had additional risk factors for venous thromboembolism (VTE) and it is difficult to be certain of the contribution of the concentrate to the VTE. In view of the recognised association between high factor VIII activity (FVIII:C) levels and VTE there is a physiological basis for this complication and it is important to consider this when administering FVIII containing concentrates to VWD patients.
Keywords: Thrombosis; concentrate; VWD